Use of DIABAX feed additive and a biogenic stimulant in calves during their rehabilitation after gastrointestinal infections - N. V. Shanshin (Ветеринария сегодня)
The results of the use of DIABAX feed additive alone and in combination with a biogenic stimulant for the correction of biochemical, hematological blood parameters in young cattle after gastrointestinal infections taking into account the disease and survival rates, as well as their performance indicators are presented. Three groups of calves at the age of less than 30 days old, two test groups and one control group, were formed for analogous pairs-based trial. Calves of control group were subcutaneously injected with saline solution at a dose of 8 mL on day 1, 5, 10 of the trial; calves of test group 1 (О-1) were fed with DIABAX feed additive with milk at a dose of 3.0 mL once a day; calves of test group 2 (О-2) were intramuscularly injected with the biogenic stimulant at a dose of 0.5 mL/10 kg of body weight on day 1, 5, 10 of the trial and also received DIABAX at a dose of 3.0 mL once a day during 15 days. The tests showed that co-administration of the biogenic stimulant and DIABAX feed additive (in О-2 group) contributed to 100% survival rate in calves, as well as significant increase in calcium and magnesium levels in animal sera by 14.5–23.8% and 61.2–79.5%, respectively, as compared with the initial levels and the levels in control group; increase in albumin and α-globulin protein fraction concentrations by 10.1% and 43.2% (p ≤ 0.05), respectively, albumin/globulin ratio – by 17.5%, color index – by 1.1%, increase in the total immunoglobulin G amount by 2.7 times as compared to the initial values. Daily administration of DIABAX feed additive to calves of О-1 group for 15 days reduced recurrent disease rate in the calves by 14.4%, resulted in significant increase in calcium and magnesium levels in sera by 10.1% and 75.0% (p ≤ 0.05), respectively, as well increase in immunoglobulin G level by 2.3 times, erythrocyte level – by 3.8%, hemoglobin level – by 8.0%, leukocyte level – by 21.8%, albumin/globulin ratio – by 35.1% in sera as compared to initial values.